2013
DOI: 10.1126/science.1239207
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Seasonal Exchange of CO 2 by Northern Ecosystems Since 1960

Abstract: Seasonal variations of atmospheric carbon dioxide (CO2) in the Northern Hemisphere have increased since the 1950s, but sparse observations have prevented a clear assessment of the patterns of long-term change and the underlying mechanisms. We compare recent aircraft-based observations of CO2 above the North Pacific and Arctic Oceans to earlier data from 1958 to 1961 and find that the seasonal amplitude at altitudes of 3 to 6 km increased by 50% for 45° to 90°N but by less than 25% for 10° to 45°N. An increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
430
3
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(481 citation statements)
references
References 68 publications
(46 reference statements)
45
430
3
3
Order By: Relevance
“…These underestimations could be explained by the underestimation by carbon cycle models of the long-term response of net ecosystem productivity to the increase in atmospheric CO 2 concentration, which in turn could be explained by our finding that models lacking explicit consideration of mesophyll diffusion underestimate the CO 2 fertilization effect. Furthermore, in the northern hemisphere, the increase in the seasonal amplitude of atmospheric CO 2 has been larger in high latitudes than in low latitudes and substantially larger than simulated by carbon cycle models (31), which agrees with our finding that the estimated CO 2 fertilization effect in the regions of >45°N is particularly sensitive to the consideration of mesophyll diffusion (Fig. 2).…”
Section: Resultssupporting
confidence: 82%
“…These underestimations could be explained by the underestimation by carbon cycle models of the long-term response of net ecosystem productivity to the increase in atmospheric CO 2 concentration, which in turn could be explained by our finding that models lacking explicit consideration of mesophyll diffusion underestimate the CO 2 fertilization effect. Furthermore, in the northern hemisphere, the increase in the seasonal amplitude of atmospheric CO 2 has been larger in high latitudes than in low latitudes and substantially larger than simulated by carbon cycle models (31), which agrees with our finding that the estimated CO 2 fertilization effect in the regions of >45°N is particularly sensitive to the consideration of mesophyll diffusion (Fig. 2).…”
Section: Resultssupporting
confidence: 82%
“…The seaonsal CO 2 amplitud increase was higher in forest ecosystems (MF, EBF and EBF), whereas there is no distinguishabel amplitude change in WSA and GRA. The same pattern appered in Graven et al (2013), with aircraft-based observation of CO 2 . Their results showed that an increased of 30%e60% in the seasonal exchange of CO 2 by northern extratropical land ecosystems, focused on boreal forests.…”
Section: Evolution and Variation Of Co 2 Concentrations At Individualmentioning
confidence: 89%
“…We also found compelling indications that change in soil moisture is an important process that modulates the temperature-productivity correlations, although the models used in this study may be presently less trusted to fully describe this. It is not straightforward to link changes in NDVItemperature relationships with changes in the net carbon balance of northern ecosystems that has an impact on seasonal 33 and spatial gradients of atmospheric CO 2 , because of the concurrent response of respiration and disturbances to temperature. Further study focusing on both the temperature dependence of vegetation productivity and ecosystem respiration and their temporal trajectory is needed.…”
Section: Discussionmentioning
confidence: 99%